Sintesis Zeolit 4A Dari Bahan Dasar Abu Limbah Sawit Dengan Variasi Lama Pengadukan Gel Dan Perbandingan Volume Natrium Silikat Dengan Natrium Aluminat - Nila Sari Siregar; Fajril Akbar; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Zeolite 4A is one of the synthetic zeolite which it is used as ion exchange. This zeolite can be synthesized from silica and alumina. This study aims to utilize the waste in the oil industry as the base material zeolite 4A synthesis and get the best conditions influence the volume ratio of reactants (sodium silicate/sodium aluminate), and long agitation in 4A zeolite synthesis process. 4A zeolite can be synthesized from the ashes of waste oil were melted with sodium hydroxide to make sodium silicate. 4A zeolite synthesis reaction process is done by mixing the reactants (sodium silicate and sodium aluminate) with variation 55:45, 60:40 and 65:35 v:v as well as the long stirring time of 1, 2 and 3 hours, followed by heating at 80 ° C for 8 hours. Zeolite synthesis results were characterized using Fourier Transform Infrared Spectrophotometry (FTIR) and X-ray Diffraction (XRD). Zeolite 4A crystallinity best result on the condition of the reactants variation 65:35 ml:ml with stirring 3 hours long and the highest ratio of 1.499.Keywords : ash waste oil, spektofotometri FTIR, XRD, zeolite 4A.